The answers are blowin' in the wind: Ultra-distal ashfall zircons, indicators of Cretaceous super-eruptions in eastern Gondwana - Barham, M.; Kirkland, Chris; Reynolds, S.; O'Leary, Mick; Evans, Noreen; Allen, H.; Haines, P.; Hocking, R.; McDonald, B.; Belousova, E.; Goodall, J. (Geological Society of America, 2016)
An Early Cretaceous siliceous large igneous province (SLIP) that developed on the eastern margin of Gondwana produced some of the most voluminous siliceous volcaniclastic deposits known globally. We report U-Pb ages and trace-element and Hf-isotopic signatures of detrital zircons from the Madura Shelf (onshore Bight Basin), Western Australia. These zircons include a geochemically distinct 106 Ma component with age and Hf characteristics that match SLIP volcanics some 2300 km distant in eastern Australia. This young subpopulation shows limited grain abrasion, which contrasts with older detrital components that are stratigraphically persistent. Regional detrital zircon provenance demonstrates that sediment routing systems were disconnected in the eastern and western Bight Basin, negating terrestrial transport mechanisms as a possible vector of the zircons from the SLIP to their recovered position. Palynology indicates that the 106 Ma zircons are syn-depositional, and we interpret them as being significantly transported in an eruption plume. Given the grain size and distance from source, such distal zircon emplacement suggests previously undocumented 106 Ma super-eruptions. The 106 Ma zircons likely reflect Southern Hemisphere winter eruptions when tropospheric polar easterly winds would have been favored across southeastern Australia.